Culex (Culiciomyia) sasai (Diptera: Culicidae), senior synonym of Cx. spiculothorax and a new country record for Bhutan - Thanari Phanitchakun (2018)
© 2017 Elsevier B.V. Culex (Culiciomyia) spiculothorax was described from Thailand based on the presence of spiculation on the thorax of larvae. Adult females are characterized but are indistinguishable from those of related species, such as Cx. pallidothorax. Phylogenetic analysis of mitochondrial oxidase subunit I (COI) sequences revealed that specimens identified as Cx. spiculothorax from Thailand, Japan and Bhutan form a single clade with Cx. sasai from Japan (Kimura 2-parameter genetic distances 0–0.9%) that is clearly distinct from clades comprised of other species of subgenus Culiciomyia. Attempts to collect Cx. sasai from several locations in Japan were unsuccessful – only larvae with thoracic vesicular-like spicules identified as Cx. spiculothorax were collected. Careful examination of specimens collected near the type locality of Cx. sasai revealed the presence of spicules on the thorax. Based on these findings, Cx. spiculothorax is formally synonymized with Cx. sasai, which replaces the former as the species present in Thailand and is a new country record for Bhutan.